A new addition to the genus Anthalona Van Damme, Sinev & Dumont, 2011 (Branchiopoda: Anomopoda: Chydoridae) - Damme, Kay Van (Zootaxa, 2016)
Continued fine-tuning of taxonomy in the Chydoridae Dybowksi & Grochowski, 1894 (Crustacea: Branchiopoda: Anomopoda) is important for the assessment of the diversity in this speciose family and our progress in chydorid biogeography and evolution. The continuation of the taxonomical study of single taxa, however tedious and seemingly unimportant, provides a fundamental basis for applied fields. Within this context, morphological studies on lesser known taxa and the establishment of their validity should continue, as so many uncertainties remain, e.g., in the lump genus Alona Baird, 1843 (Van Damme et al. 2010). Recent studies suggest that we are still far from a realistic image on cladoceran diversity, in particular for the Chydoridae (Forró et al. 2008, Van Damme et al. 2010). The current correspondence discusses the validity and the position of a single species, Alona milleri Kiser, 1948, originally described from the Pearl River, China (Kiser 1948).